Hepatoprotective Models and Various Natural Product Used in Hepatoprotective Agents: a Review - Bansal, Jharna; Kumar, Nitin; Malviya, Rishabha; Sharma, Pramod Kumar (Pharmacognosy Communications)
Liver is involved in several vital functions such as metabolism, secretion, and storage as well as detoxification of several drugs and xenobiotics occurs in the liver itself because it is the most vital organ of the body. India is also called as “Botanical Garden Of World”. Conventional medicine is now pursuing the use of natural products such as herbs to provide the support that the liver needs on a daily basis. Many Ayurvedic herbs, such as andrographis, have a long history of traditional use in revitalizing the liver and treating liver dysfunction and disease. Medicinal plant contain certain phytochemicals which posses anti-oxidant activity. Development and scientific studies have validated such herbal medicines or combinations confirming the safety and biological efficacy which is helpful in neutralizing the liver disorder.
Keywords: hepatoprotective; herbal medicines; hepatitis; natural product; hepatic model